Delivery of Aerosolized Bronchodilators by High-Flow Nasal Cannula During COPD Exacerbation - Colaianni-Alfonso, Nicolás; MacLoughlin, Ronan; Espada, Ariel; Saa, Yasmine; Techera, Mariano; Toledo, Ada; Montiel, Guillermo; Castro-Sayat, Mauro (Respiratory care, 2023)
Bronchodilator delivery via a high-flow nasal cannula (HFNC) has generated interest in recent years. The efficacy of in-line vibrating mesh nebulizers with an HFNC during COPD exacerbation is limited. The aim of this study was to evaluate the clinical response of subjects with COPD exacerbation who require bronchodilator therapy (anticholinergic and β-agonist) by using a vibrating mesh nebulizer in line with an HFNC. This was a prospective single-center study performed in a respiratory intermediate care unit that enrolled patients with a diagnosis of COPD exacerbation who required noninvasive ventilation on admission. All the subjects underwent noninvasive ventilation breaks with an HFNC. After clinical stability, pulmonary function tests were performed to assess changes in FEV and clinical parameters before and after bronchodilation by using a vibrating mesh nebulizer in line with an HFNC. Forty-six patients with COPD exacerbation were admitted. Five patients who did not use noninvasive ventilation and 10 patients who did not receive bronchodilator treatment with a vibrating mesh nebulizer were excluded. Thirty-one were selected, but 1 subject was secondarily excluded due to loss of data. Finally, 30 subjects were included. The primary outcome was spirometric changes in FEV . The mean ± SD FEV before receiving bronchodilator treatment by using a vibrating mesh nebulizer in line with an HFNC was 0.74 ± 0.10 L, and, after receiving treatment, the mean ± SD FEV changed to 0.88 ± 0.12 L ( < .001). Similarly, the mean ± SD FVC increased from 1.75 ± 0.54 L to 2.13 ± 0.63 L ( < .001). Considerable differences were observed in breathing frequency and heart rate after receiving bronchodilator treatment. No relevant changes were observed in the Borg scale or S after treatment. The mean clinical stability recorded was 4 d. In subjects with COPD exacerbation, bronchodilator treatment by using a vibrating mesh nebulizer in line with an HFNC showed a mild but significant improvement in FEV and FVC. In addition, a decrease in breathing frequency was observed, suggesting a reduction in dynamic hyperinflation.